(untitled) (Research, Society and Development, 2024)
Created in the municipality of Igarapé-Miri, in the interior of Pará, Mirimbol and Contrataque are the focus of this investigation. The objective was to analyze the knowledge of elementary school students regarding these two modalities in Santana, Amapá. The study was carried out with an exploratory and descriptive nature, with a sample of 200 students. In data collection, a questionnaire was used to verify the students’ knowledge regarding the modalities researched. It was found in the results that in the reality investigated, little is known about these sports and they are still confused with game content. Most participants are unaware of the technical, historical aspects and specific characteristics of the two modalities investigated. It is concluded that it is necessary to consider regionalities in studies of this nature because it reveals the peculiarities of the national reality and the contribution of these sports, diversifying the content offered to students.